2017
DOI: 10.1186/s12985-017-0864-8
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of porcine microRNAs in African swine fever virus infected pigs: a proof-of-concept study

Abstract: BackgroundAfrican swine fever (ASF) is a re-expanding devastating viral disease currently threatening the pig industry worldwide. MicroRNAs are a class of 17–25 nucleotide non- coding RNAs that have been shown to have critical functions in a wide variety of biological processes, such as cell differentiation, cell cycle regulation, carcinogenesis, apoptosis, regulation of immunity as well as in viral infections by cleavage or translational repression of mRNAs. Nevertheless, there is no information about miRNA e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 59 publications
3
20
1
Order By: Relevance
“…The effect of African swine fever virus (ASFV) infection on pig miRNAs has been investigated in vivo by comparing miRNA expression in animals infected with two viral strains (virulent vs. attenuated) (131). Ten miRNAs were selected for target prediction based on the highest representation by tissue and conditions, namely, miR-23a, miR-30e-5p, miR-92a, miR-122, miR-125b, miR-126-5p, miR-145-5p, miR-125a, miR-451, and miR-126-3p.…”
Section: Immunitymentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of African swine fever virus (ASFV) infection on pig miRNAs has been investigated in vivo by comparing miRNA expression in animals infected with two viral strains (virulent vs. attenuated) (131). Ten miRNAs were selected for target prediction based on the highest representation by tissue and conditions, namely, miR-23a, miR-30e-5p, miR-92a, miR-122, miR-125b, miR-126-5p, miR-145-5p, miR-125a, miR-451, and miR-126-3p.…”
Section: Immunitymentioning
confidence: 99%
“…Ten miRNAs were selected for target prediction based on the highest representation by tissue and conditions, namely, miR-23a, miR-30e-5p, miR-92a, miR-122, miR-125b, miR-126-5p, miR-145-5p, miR-125a, miR-451, and miR-126-3p. The putative target genes were related to immune responses, such as B and T cell receptor signaling pathways, natural killer cell-mediated cytotoxicity, or Fc gamma R-mediated phagocytosis, as well as with processes related to infection-related pathogenesis and virus-host interaction (131). In another in vivo study, the same authors assessed the potential for ASFV to encode its own miRNAs, with negative results (132).…”
Section: Immunitymentioning
confidence: 99%
“…Whereas infection with the attenuated E75CV1 strain was associated with an upregulation of genes encoding proteins involved in the activation of different innate immune pathways, infection with the virulent E75 strain was associated with the downregulation of the expression of genes encoding SERPINA3, induced during inflammation, or vitamin Dbinding protein involved in macrophage activation and inflammation. 152,153 In addition, the study by deep sequencing of microRNA gene expression in spleen and submandibular lymph nodes infected with virulent and attenuated ASFV strains revealed modifications in microRNAs (miRNAs) expression patterns. Indeed, miR-23a, miR-92a, miR-122, miR-125a, miR-125b, miR-126-5p, miR-30e-5p, miR-451, and miR-145-5p were either up or downregulated during infection with the virulent E75 viral strain.…”
Section: Hijacking Of Antiviral Responses May Be Essential For Giant mentioning
confidence: 99%
“…The effect of ASFV infection on host miRNAs has been investigated in vivo by comparing miRNA expression in pigs infected with a virulent strain to those infected with an attenuated strain ( 30 ). These authors identified 12 miRNAs that were differentially expressed.…”
Section: Introductionmentioning
confidence: 99%